A randomised controlled trial comparing immediate versus delayed catheter removal following vaginal prolapse surgery. (March 2017) - Bray, Rhiannon; Cartwright, Rufus; Digesu, Alex; Fernando, Ruwan; Khullar, Vik
Abstract: Objective: It is unclear if any catheterisation is necessary after vaginal surgery for pelvic organ prolapse. The aim of this study was to determine if indwelling catheterisation is necessary after these procedures. Study design: A randomised controlled trial of immediate post-operative removal of catheter compared to a suprapubic catheter (SPC) after vaginal prolapse surgery. In the Suprapubic group the catheter was left on free drainage until a voiding trial was commenced at 48 h. Women in the immediate removal group underwent in/out catheterisation only if they had not voided by 8 h after surgery to ensure the bladder did not over-distend. Results: 55% (n = 17) of patients in the immediate removal group did not require catheterisation postoperatively. A further 13 (42%) patients only required one in/out catheterisation 8 h post operatively. In the immediate removal group duration of catheterisation was significantly shorter (median 0 h, IQR 0–8 h, range 0–16 h) vs (6 days (IQR 2-8 days, range 2–19 h) p = 0.001). The duration of hospital stay (7 days (range 3–16) vs. 9 (range 3–27) p = 0.014), day of first mobilisation (Day 1, range 0–2, vs. Day 2, range 1–4, p = 0.001), and rate of Symptomatic bacturia (16% vs. 52%, p < 0.01) were all significantly better with immediate catheter removal. Conclusions: After vaginal surgery for pelvic organ prolapse, the majority of patients do not require extended catheterisation. Early removal of a catheter reduces urinary tract infection and significantly decreases hospital stay. Such a policy should result in improved patient satisfaction and reduced hospital costs.